PEMANTAU SUHU DENGAN RF BERBASIS KOMUNIKASI SERIAL MENGGUNAKAN LABVIEW - , AGIL RISNANDA JALU ASMORO P; , Drs. Panggih Basuki, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
It has been made a temperature monitoring system with RF based serial communication using LabVIEW. The design of the system uses temperature sensor, radio frequency, microcontroller and USB to Serial converter. Temperature sensor detected the temperature changing which is received and it produced voltage value and then processed by microcontroller, the temperature data will be sent by using radio frequency waves and received by the USB to Serial converter that will be proceed the data through a computer. The work performance of this instrument is a temperature monitoring can be done at a distance of less than 40 meters. The information is given current temperature, chart, extreme heat temperature, extreme cold temperature, maximum temperature, minimum temperature, and the average temperature during the measurement. Overall the system can perform retrieval temperature data in one second. From the result of testing the system are known, that this tool can work as well. This is evidenced by the temperature sensor deviation of 0,22 0C and effective measurements at distances less than 12 meters. This tool is made in order to assist in the management of monitoring room temperatures that have the efficiency and can be access by computer.